Lacrimal canaliculitis related to chronic rhinosinusitis with nasal polyps: Case report and literature review - Chen Chen; Yan Shen; Yanting Yang; Yuru Gao; Yang Bian (SAGE Open Medical Case Reports)
This paper reports an unusual case of recurrent canaliculitis who had a long history of chronic rhinosinusitis with nasal polyps. A 74-year-old woman complained of recurrent redness, purulent discharge, and occasional tearing of the left eye for 1 year. She has a 40-year untreated sinusitis history, with recurrent mucopurulent rhinorrhea, nasal obstruction and hyposmia, and loss of smell for 2 years. The patient’s various symptoms, such as epiphora, purulent discharge, rhinorrhea, nasal obstruction, and anosmia, poorly responded to antibiotics and canaliculotomy. However, relief came from the unintentional usage of systemic corticosteroids. Canaliculitis is a rare form of inflammation involving the proximal lacrimal drainage system. Unfortunately, it is often misdiagnosed, has frequent recurrences, and fails to respond to therapy. This case highlights the importance of medical history, lacrimal examinations, and regular therapy in managing recurrent canaliculitis. For those canaliculitis patients with nasal symptoms, simultaneous treatment of nasal-related disorders should be considered.